Impact, Utilization and Applications of Digital Media for Government in Rural Settings. A Comparative US-Romania Research - Tudor Vlad; Cristina Hințea; Bogdana Neamțu; Viorel Stănică (Transylvanian Review of Administrative Sciences, 2023)
Abstract Interaction between citizens and government has traditionally taken place in community settings, government meetings, special town hall meetings, written correspondence in letters, emails, or texts, or via a phone call to a government representative. With digital media, citizens can instantly interact with the government. The mobile component of digital media will continue to be important in this interaction. This research operates with the assumption that digital media expresses a paradigmatic shift regarding how to govern and how to communicate. Digital media clearly is transforming the way governments think, plan, and carry out their policies but more importantly, how they communicate public policy. Our research intends to understand how local government institutions in rural settings use digital media and other communication channels to communicate with their citizens. The research employs a comparative perspective by investigating rural communities from the US and Romania. This was achieved by undertaking a content analysis of local government’s websites and social media platforms, as well as collecting primary data through interviews with representatives of local government, to assess the ways they use digital media, traditional media, and other communication tools, and whether they viewed them as effective strategies.